2014
DOI: 10.1136/postgradmedj-2013-132215
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain after surgery: pathophysiology, risk factors and prevention

Abstract: Interest in chronic pain after surgery has grown since the finding that more than a fifth of patients attending chronic pain clinics cite surgery as the cause for their chronic pain. The problem is not limited to major surgery; even common minor procedures such as hernia repair have a significant risk of chronic pain. Surgical technique can influence the development of chronic postsurgical pain (CPSP) and techniques to minimise nerve injury should be used where possible. Central nervous system changes contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 50 publications
11
121
1
15
Order By: Relevance
“…Maka, kerusakan saraf intraoperatif harus diminimalkan, guna mencegah terjadinya nyeri kronis. 16 Salah satu teknik operasi yang dapat diterapkan untuk mengurangi nyeri kronis pasca operasi adalah teknik laparoskopi. 17 Pengalaman dari seorang ahli bedah, yaitu dalam teknik operasi dalam meminimalisir kerusakan saraf dan lebih tingginya tingkat unit operasi mempengaruhi terjadinya nyeri kronis.…”
Section: Operasi Sebagai Faktor Risiko Dan Pencegahannyaunclassified
See 1 more Smart Citation
“…Maka, kerusakan saraf intraoperatif harus diminimalkan, guna mencegah terjadinya nyeri kronis. 16 Salah satu teknik operasi yang dapat diterapkan untuk mengurangi nyeri kronis pasca operasi adalah teknik laparoskopi. 17 Pengalaman dari seorang ahli bedah, yaitu dalam teknik operasi dalam meminimalisir kerusakan saraf dan lebih tingginya tingkat unit operasi mempengaruhi terjadinya nyeri kronis.…”
Section: Operasi Sebagai Faktor Risiko Dan Pencegahannyaunclassified
“…16 tulang belakang ke arah belakang dapat menyebabkan terjadinya patah tulang dan kelumpuhan. Pada keadaan tersebut, timbul suatu antisipasi yang seharusnya merupakan suatu respons yang baik untuk menghindari hal yang buruk, akan tetapi kebiasaan berpikir negatif menyebabkan antisipasi tersebut menjadi suatu hal yang salah.…”
Section: Faktor Psikososialunclassified
“…It may possibly prevent the barrage of nociceptive inputs into the dorsal horn preventing central sensitization by minimizing the transmission of signals to or within the spinal cord. Peripheral nerve blocks and would infiltrations interrupt impulses in peripheral nerves whereas Subarachanoid block and edpiural block techniques act on the nerve roots [1]. A Cochrane review done among 23 RCTs and data pooled from 250 patients in three trials, found that epidural anesthesia for thoracotomy to be beneficial in reducing the risk of chronic pain at 6 months [4].…”
Section: Regional Anesthesia and Analgesic Consideration Affecting Cpopmentioning
confidence: 99%
“…There are several risk factors which result in Chronic postoperative pain including preoperative, intraoperative and postoperative [1]. In case of abdominal surgeries, pain is due to incision in abdominal or visceral wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation